IoTHunter: IoT network traffic classification using device specific keywords. Issue 2 (12th January 2021) - Khandait, Pratibha; Hubballi, Neminath; Mazumdar, Bodhisatwa
Abstract: With the proliferation of IoT devices, network management and security monitoring are becoming a challenge. For the timely detection of IoT device status and their behaviour, traffic classification methods are used. Herein, IoTHunter, a Deep Packet Inspection based IoT traffic classifier, is described. It extracts unique keywords comprising domain names, device names etc. to identify flows belonging to a particular device. IoTHunter automates the keyword extraction using the frequency of occurrence of words belonging to flows of different devices. To further enhance the performance, IoTHunter combines device specific keywords with MAC address of device for subsequent flow labelling. A publicly available IoT dataset is experimented and a good classification accuracy of it over a range of IoT devices is demonstrated.